TUTUPAN LAHAN GAMBUT MEMPENGARUHI KONDISI IKLIM MIKRO DI SEKITAR KAMPUS UNIVERSITAS PALANGKA RAYA (Preliminary Data Integrasi Wireless Sensor Network) The Peatland Cover Impact Micro Climate Conditions Near Campus of the University of Palangka Raya (Preliminary Integration Data of Wireless Sensor Network) - F.A., Adji; R., Teguh (AGRIPEAT, 2018)
ABSTRACTÂ The lack of field measurements, which collected in long period and significantly spatial effect on the environments can obstruct scientific understanding the effect of environmental condition on the ecosystems. Application wireless sensor network (WSN) is useful to address the situation through low cost wireless measurement sensors and minimize disruption to the location/conditions to be monitored. The comprehension of composition transformation, structure, the environment ecosystems dynamic, and how is the transformation of all can be affecting the human life, indeed this challenge are need detail analysis of all environment ecosystem elements. This study also review the uses of smart devices wireless sensor networks (WSN), and observe the underlying technology in hopes could be giving solve or determine the condition of environment and ecosystems affected by human activity. The results of this study showed that the land use cover is influence on the environment conditions.Â Keywords: Wireless sensor networks (WSN), ecosystems, and environment